Legal standards of milk delivered for processing in Brazil - Samera R Bruzaroski; Italo B Trento; Sarah Rezende; Flavia AB Pereira; Bruno G Botaro; Joice Sifuentes dos Santos; Agostinho Ludovico; Elsa H W Santana (Bioscience Journal, 2017)
Thresholds for Somatic Cell Counts (SCC) and Total Bacterial Counts (TBC) in refrigerated raw milk have been stricter in Brazil since July 2014. We evaluated whether the composition of 11,051 milk samples delivered to processing plants in Paraná state, Brazil, by cooperative dairy farms, complies with government requirements and established changes. Milk quality was evaluated from June to August 2014, from dairy farms in three states. Data were obtained by infrared spectroscopy and flow cytometry. SCC was highest in June (p<0.05), when the highest number of samples and mean values was observed that did not comply with legal standards. No samples obtained in July complied with the requirements. The city in Mato Grosso do Sul state was the only one that met the legal requirements throughout the period studied. TBC did not vary (p>0.05) in the trimester, and none of the cities presented values below the maximum TBC allowed. Protein, fat and non-fat solids obtained complied with legal requirements. Total solids and lactose varied among the months (p<0.05), with highest values for total solids in June and for lactose in August. Milk samples did not comply with minimal requirements for SCC and TBC, and were not adjusted to more rigid quality standards.